2015
DOI: 10.1186/s12889-015-2399-5
|View full text |Cite
|
Sign up to set email alerts
|

Social support and dairy products intake among adolescents: a study from Iran

Abstract: BackgroundAdequate daily milk and dairy products intake seems to an important for adolescents’ health. This study aimed to identify the high-risk group adolescents who did not meet the recommended daily serving milk and dairy products and indeed to find out associated factors relating to their nutrition behaviors.MethodsThis cross sectional study was carried out on 7th grade students, in Tabriz, East Azerbaijan province, Iran. An anonymous self–administrated questionnaire including items on perceived social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 36 publications
0
28
1
Order By: Relevance
“…In addition, Cronbach's alpha of the Health Knowledge subscale (0.41) and the pFAS (0.65) were both low, which may be due to low number of questions, heterogeneous constructs, or poor inter-relatedness between items. 55 In the original papers on the development of IHLQ 20 and translation of pFAS, 23 the authors reported none and 0.88, respectively, as Cronbach alpha for the scales. In our study, poor Cronbach alpha for both scales seems to be due to heterogeneous items and constructs of the scales, which need more investigations in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Cronbach's alpha of the Health Knowledge subscale (0.41) and the pFAS (0.65) were both low, which may be due to low number of questions, heterogeneous constructs, or poor inter-relatedness between items. 55 In the original papers on the development of IHLQ 20 and translation of pFAS, 23 the authors reported none and 0.88, respectively, as Cronbach alpha for the scales. In our study, poor Cronbach alpha for both scales seems to be due to heterogeneous items and constructs of the scales, which need more investigations in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The family socio-economic status was determined by using Persian family affluence scale (FAS). 23 This scale comprises five different properties: family car ownership, computer and laptop ownership, number of rooms excluding kitchen and bathrooms, number of telephones, and having or not having unshared bedroom. This scale has an overall score range of 0-13, and categorized as low (score of 0-4), moderate (score of 5-8) and high (score of 9-13).…”
Section: Methodsmentioning
confidence: 99%
“…Demographic data consisted of questions regarding patient's age, sex, education level, occupation, household size, and socioeconomic status. Socioeconomic status was determined by the valid family affluence scale based on existence or nonexistence of ordinary household items, scoring from 0 to 1 and above [28]. Summing up of scores was categorized under 2 groups: low and moderate (0-14) and high (15-23).…”
Section: Data Collectionmentioning
confidence: 99%
“…Socio-economic status of the families were determined by the valid family affluence scale (FAS) [33,34]. It contained 14 common household properties: private bedroom, laundry, dishwasher, TV set, personal computer (PC), laptop, tablet, landline telephone, smartphone, and access to internet network.…”
Section: Data Collection and Measuresmentioning
confidence: 99%